Method of Prevention of Fracture of Welded Metal Structural Elements Subjected to Single Dynamic Loads - Kir’yan, V.I.; Shamanovskii, S.V. (Проблемы прочности, 2002)
Method of assessment of fracture toughness of structural materials and their welded joints under the conditions of a single dynamic loading has been suggested on the basis of criterion of a non-linear fracture mechanics δcr^D(CTOD). The regularities of effect of loading rate, determined by parameter δ' (rate of crack tip opening) on the fracture toughness were established. Procedure of prevention of fracture of welded structure elements at a high-strength deforming was recommended. На основе критерия нелинейной механики разрушения δcr^D (CTOD) предложена методика оценки вязкости разрушения конструкционных материалов и их сварных соединений в условиях однократного динамического нагружения. Установлены закономерности влияния скорости нагружения, определяемой параметром δ' (скорость раскрытия вершины трещины), на вязкость разрушения. Рекомендована методика предупреждения разрушений элементов сварных конструкций при высокоскоростном деформировании. На основі критерію нелінійної механіки руйнування δcr^D (CTOD) запропоновано методику оцінки в’язкості руйнування конструкційних матеріалів і 'їхніх зварних з’єднань в умовах одноразового динамічного навантаження. Установлено закономірності впливу швидкості навантаження, що визначається параметром δ' (швидкість розкриття вістря тріщини), на в’язкість руйнування. Рекомендовано методику попередження руйнування елементів зварних конструкцій за високошвидкісного деформування.